1951
DOI: 10.1136/jcp.4.3.360
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spermine in the Inhibition ofStaphylococcus aureusby Human Semen

Abstract: The inhibitory activity of human semen on the growth of Staphylococcus aureus has been reported previously (Rozansky, Gurevitch, Brzezinsky, and Eckerling, 1949).The Function of Human Semen The investigation has now been extended using 12 addi.ional freshly isolated strains of Staph. aureus.Materials and Methods.-Seventy-five specimens of semen from 53 patients (of the male sterility clinic) between the ages of 23 and 51 years were examined. Six of these were azoospermic, 25 oligospermic (less than 60 million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1955
1955
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Spermine and spermidine are known to inhibit the growth of various bacteria (Gurevitch, Rozansky, Weber, Brzezinsky & Eckerling, 1951 ;Rozansky, Bachrach & Grossowicz, 1954) and fungi (Razin, Cohen, Rozansky, 1958). As both sensitive and resistant bacteria absorb these polyamines (Razin & Rozansky, 1959), the selective toxicity is not explained by absorption alone.…”
Section: Discussionmentioning
confidence: 99%
“…Spermine and spermidine are known to inhibit the growth of various bacteria (Gurevitch, Rozansky, Weber, Brzezinsky & Eckerling, 1951 ;Rozansky, Bachrach & Grossowicz, 1954) and fungi (Razin, Cohen, Rozansky, 1958). As both sensitive and resistant bacteria absorb these polyamines (Razin & Rozansky, 1959), the selective toxicity is not explained by absorption alone.…”
Section: Discussionmentioning
confidence: 99%
“…Here we are interested in the potential application of biogenic polyamines, a group of small polycationic compounds widely distributed in prokaryotic and eukaryotic cells (8), to enhancing the bacterial susceptibility to ␤-lactam antibiotics. While spermine (a tetraamine) at high concentrations was reported to exert an intrinsic antibacterial activity in S. aureus (12), our previous studies have demonstrated the capability of exogenous spermine at low concentrations to reverse MRSA susceptibility to ␤-lactams (20). However, the molecular mechanism of this strong synergistic effect by spermine and ␤-lactams in S. aureus was still unclear.…”
mentioning
confidence: 89%
“…It has also been suggested that, as spermine is endowed with bacteriostatic properties against certain micro-organisms such as Staphylococcus aureus, it may be responsible for the inhibitory effect which human seminal plasma is known to exert on microbial growth (Gurevitch, Rozansky, Weber, Brzezinsky & Eckerling, 1951;Grossowicz, Razin & Rozansky, 1955). But one must bear in mind that human seminal plasma abounds in a variety of proteolytic, nucleolytic and other hydrolytic enzymes some of which may also be capable of interfering with bacterial growth.…”
Section: Secretory Mechanismsmentioning
confidence: 99%